Different Renal Function Patterns in Patients With Acute Heart Failure: Relationship With Outcome and Congestion - Palazzuoli, Alberto; Crescenzi, Federico; Luschi, Lorenzo; Brazzi, Angelica; Feola, Mauro; Rossi, Arianna; Pagliaro, Antonio; Ghionzoli, Nicolò; Ruocco, Gaetano (Frontiers in Cardiovascular Medicine, 2022)
Background-The role of worsening renal function during acute heart failure (AHF) hospitalization is still debated. Very few studies have extensively evaluated the renal function (RF) trend during hospitalization by repetitive measurements. Objectives- to investigate the prognostic relevance of different RF trajectories together with the congestion status in hospitalized patients. Methods- This is a post-hoc analysis of a Multi-centers study including 467 patients admitted with AHF who were screened for the Diur-AHF Trial. We recognized five main RF trajectories based on serum creatinine and estimated glomerular filtration rate (eGFR) behavior: according to the RF curve our sample was divided into 1-stable (S), 2-transient improvement (TI), 3-permanent improvement (PI),4- transient worsening (TW) and 5-persistent worsening (PW). The primary outcome was the combined endpoint of 180 days including all causes of mortality and re-hospitalization. Results- we recruited 467 subjects with a mean congestion score of 3.5±1.08 and a median creatinine value of 1.28 [1.00-1.70] mg/dl, eGFR 50 [37-65] ml/min /m2 and NTpro BNP 7000 [4200-11700] pg/mL. A univariate analysis of the RF pattern demonstrated that TI and PW patterns were significantly related to poor prognosis (HR: 2.71 [1.81-4.05]; p<0.001; HR: 1.68 [1.15-2.45]; p=0.007, respectively). Conversely, the TW pattern showed a significantly protective effect on outcome (HR: 0.34[0.19-0.60]; p<0.001). Persistence of congestion and BNP reduction ≥ 30% were significantly related to clinical outcome at univariate analysis (HR: 2.41[1.81-3.21]; p<0.001 and HR: 0.47[0.35-0.67]; p<0.001). A multivariable analysis confirmed the independently prognostic role of TI, PW patterns, persistence of congestion and reduced BNP decrease at discharge. Conclusions- Various RF patterns during AHF hospitalization are associated with different risk(s). PW and TI appear to be the two trajectories related to worse outcome. Current findings confirm the importance of RF evaluation during and after hospitalization.